Design and Fabrication of Sheet Metal Cutting Machine - Sundramurthy, Ghugan; Jamian, Rahim (Progress in Engineering Application and Technology, 2024)
The main goal of this research project is to create an automated sheet metal cutting device that is suitable for small-scale industry requirements. The machines that are currently on the market are renowned for their large size and expensive hydraulic or pneumatic systems, which lead to high maintenance costs. However, there are a lot of safety and precision issues with handheld manual cutters. Our suggested prototype will make use of the effectiveness of a pneumatic system and be painstakingly designed using state-of-the-art Solid Works software to solve these problems. Our invention will be used at a small business’s metal fabrication worksite to verify its functionality